2014
DOI: 10.1007/s00449-014-1316-0
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-catalyzed production of biodiesel by ultrasound-assisted ethanolysis of soybean oil in solvent-free system

Abstract: This work reports the transesterification of soybean oil with ethanol using a commercial immobilized lipase, Novozym 435, under the influence of ultrasound irradiation, in a solvent-free s. The experiments were performed in an ultrasonic water bath, following a sequence of experimental designs to evaluate the effects of temperature, enzyme and water concentrations, oil to ethanol molar ratio and output irradiation power on the reaction yield. Besides, a kinetic study varying the substrates molar ratio and enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…Also, there have been some reports related to the use of ultrasound of lipase catalyzed biodiesel production. Trentin et al [8] reported the transesterification of soybean oil with ethanol using a commercial immobilized lipase, Novozym 435, under the influence of ultrasound irradiation, in a solvent-free system. Also, the production of fatty acid ethyl esters (FAEE) by means of Macauba (Acrocomiaaculeata) coconut oil (MCO) in solvent-free enzymatic transesterification reactions using a commercial immobilized lipase (Novozym 435) under the influence of ultrasound irradiation has been reported by Michelin et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there have been some reports related to the use of ultrasound of lipase catalyzed biodiesel production. Trentin et al [8] reported the transesterification of soybean oil with ethanol using a commercial immobilized lipase, Novozym 435, under the influence of ultrasound irradiation, in a solvent-free system. Also, the production of fatty acid ethyl esters (FAEE) by means of Macauba (Acrocomiaaculeata) coconut oil (MCO) in solvent-free enzymatic transesterification reactions using a commercial immobilized lipase (Novozym 435) under the influence of ultrasound irradiation has been reported by Michelin et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these drawbacks, several studies suggest the use of lipases for enzymatic transesterification of triglycerides as an interesting alternative to the alkaline process . Compared to the conventional reaction of biodiesel production, the enzymatic route is considered a “greener reaction” due to its environmental benefits, since there is no generation of alkaline wastewater, as well as washing steps for catalyst removal being unnecessary .…”
Section: Introductionmentioning
confidence: 99%
“…Estes resultados mostram se superiores ao encontrados na literatura por Trentin (2013) que avaliou o uso de Novozym 435 em ciclos repetidos de metanólise de óleo de canola em sistema livre de solvente, observou que depois de 5 ciclos de 432 horas de reação, a conversão foi mantida a 97 %, mas, infelizmente, a atividade da enzima não foi relatada em tal trabalho de investigação. Naturalmente, a estabilidade da enzima é um parâmetro e estudos adicionais relevantes devem ser realizados para melhorar a imobilização de enzimas de poliuretano para fins práticos.…”
Section: Resultados E Discussõesunclassified